Can Corporate Diversification Mitigate the Negative Impact of Economic Policy Uncertainty on Firm Value? : (A Case Study of Three Countries: Indonesia, Malaysia, and Thailand) (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study investigates the impact of economic policy uncertainty (EPU) on firm value and examines the role of corporate diversification between EPU and firm value. The research utilizes data from food and beverage companies in three countries Indonesia, Malaysia, and Thailand covering the period from 2019 to 2023, with 530 observations from 106 companies. It employs index-based measures for EPU and corporate diversification. Data is processed using Eviews 12, with the selected regression analysis model being the Random Effect Model (REM). The results indicate that diversification has a positive and significant effect on firm value, while EPU does not have a significant influence. Additionally, diversification cannot moderate the negative effects of EPU on firm value. Control variables positively influence firm value, including dividends, debt ratio, and operating cash flow.